Paradox and the Dissolution of the Problem of Clarity in Wittgenstein's Tractatus Logico-Philosophicus - Jenkins, Anthony David (My University, 1993)
The present thesis emphasizes one among many themes developed in Wittgenstein's TLP, namely, the elucidation of the symbolism's of colloquial languages and logically canonical notations. In accordance with this emphasis, I have read the Tractatus as providing initially a solution and ultimately an attempted dissolution of one key philosophical problem, what I have called the problem of clarity: PC' The problem as to how the symbols of a language must stand to one another and to the rest of reality so that what can be said can be said clearly. The argument of the thesis, then, consists of two parts. The first shows how Wittgenstein's pictorial account of propositions proffers a solution to PC' under the constraint of the following three main assumption: Realism Thesis (RT) The meanings of symbols have being: they are either eternal, or temporal entities. Independence Thesis The being of entity without exception language or thought. (1..I) es does depend not upon at being least meant not in A2 (Adequacy Thesis) The canons of grammar and diction of colloquial languages are adequate for determining the canons of clarity (that is, the canons with respect to which what is said is counted as clearly or unclearly said), where these canons are directly understood to be logical canons. The second shows how through his criticisms -under RT and 1..1. of Russell's theory of types and theories of judgement, Wittgenstein commits himself and his sympathetic reader to an ultimate distinction between what can be said and what can be shown. This distinction directly gives rise to the paradox of TLP that according to the elucidation Wittgenstein gives of sentences with sense, the sentences of TLP must themselves lack sense. Accordingly, it is through his commitment to this paradox that Wittgenstein ceases to recognize Pc·, and other philosophical problems, as questions deserving of an answer in terms of propositions. This is how the problem of clarity purportedly receives its dissolution, at least when this problem is taken under the assumption of RT, IT and the assumption of the contingency of all facts.
Keywords: Wittgenstein's; Tractatus Logico-philosophicus